2021
DOI: 10.3389/fcvm.2021.740531
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the PD-1 Pathway Decreases Atherosclerotic Lesion Development in Ldlr Deficient Mice

Abstract: Aim: Signaling through the coinhibitory programmed death (PD)-1/PD-L1 pathway regulates T cell responses and can inhibit ongoing immune responses. Inflammation is a key process in the development of atherosclerosis, the underlying cause for the majority of cardiovascular diseases. Dampening the excessive immune response that occurs during atherosclerosis progression by promoting PD-1/PD-L1 signaling may have a high therapeutic potential to limit disease burden. In this study we therefore aimed to assess whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…Mice deficient in both PD-L1 and PD-L2 show increased atherosclerosis (25). Similarly, PD-1 knockout mice or mice treated with a PD-1 blocking antibody developed exacerbated atherosclerosis (26,27), whereas stimulation of PD-1 signaling reduces atherosclerosis (28). Our data is further supported by previous studies that demonstrated the proatherogenic role of T FH cells (12)(13)(14).…”
Section: Discussionsupporting
confidence: 88%
“…Mice deficient in both PD-L1 and PD-L2 show increased atherosclerosis (25). Similarly, PD-1 knockout mice or mice treated with a PD-1 blocking antibody developed exacerbated atherosclerosis (26,27), whereas stimulation of PD-1 signaling reduces atherosclerosis (28). Our data is further supported by previous studies that demonstrated the proatherogenic role of T FH cells (12)(13)(14).…”
Section: Discussionsupporting
confidence: 88%
“…Previously the association between ICI and the progression of atherosclerosis has been highlighted (9,13). In our study, we observed an increase in the percentage of patients with atherosclerotic lesions in the common carotid artery after 3 months.…”
Section: Discussionsupporting
confidence: 68%
“…Exhausted T cells lose some of their effector functions, and thereby potentially also their pro-atherogenic role. For example, stimulation of the main immune checkpoint for T cell exhaustion, PD-1, decreases the formation of atherosclerotic lesions in mice by reducing T cell activation and proliferation ( 51 ). Moreover, Bazioti et al.…”
Section: Discussionmentioning
confidence: 99%